Comparing in vitro and in vivo virulence phenotypes of Burkholderia pseudomallei type G strains. - Eric R G Lewis; Paul B Kilgore; Tiffany M Mott; Gonzalo A Pradenas; Alfredo G Torres (PLoS ONE, 2017)
Burkholderia pseudomallei (Bpm) is a saprophytic rod-shaped gram-negative bacterium and the causative agent of melioidosis. This disease has previously been described as endemic in areas such as northern Australia and Southeast Asia, but, more recently, a better understanding of the epidemiology of melioidosis indicated that the disease is distributed worldwide, including regions of the Americas and Africa. A 16S-23S rDNA internal transcribed spacer (ITS) typing system has been developed for Bpm and has revealed that ITS types C, E, and hybrid CE are mainly associated with Australia and Southeast Asia while type G strains are more associated with cases of melioidosis in the Western Hemisphere. The purpose of the current study was to determine the in vitro and in vivo virulence profiles of the understudied Bpm type G strains Ca2009, Ca2013a, Mx2013, and 724644 and compared such phenotypes to the commonly studied Bpm type C strain K96243. We evaluated virulence by measuring invasion/uptake and survival of these Bpm strains in murine respiratory epithelial LA-4 cells and alveolar macrophage MH-S cells using different multiplicity of infections (MOIs of 1 and 10). We also calculated the lethal dose 50 values (LD50) in BALB/c mice that were inoculated intranasally with either Ca2009, Ca2013a, or Mx2013. Overall, the virulence and lethality phenotypes of Bpm type G strains were similar to the Bpm type C strain K96243. Additional comparative analyses between the Bpm ITS types may lead to a better understanding of the contribution of the ITS type to the epidemiology and ecology of Bpm strains.